Identification of Common Risk Factors Associated with Carpal Tunnel Syndrome (Bangladesh Journal of Neuroscience, 2013)
Objective: To identify the common risk factors associated with carpal tunnel syndrome.Methodology:This case-control observational study was conducted in the department of neurology and medicine, DMCH from May 2010 to April 2011 for a duration of 1 year. The study included purposively selected 80 persons. Patients attending the outdoor and admitted in indoor of department of neurology and medicine, DMCH with a clinically suspected CTS and established by electrophysiological parameters selected as cases (group –I) . Healthy volunteers and subjects who were devoid of any features of CTS but having history with isolated injury to the lower limb nerve and isolated facial nerve palsy with normal electrophysiological parameters selected as control (group –II). Data were collected by interview of the patients, clinical examination and laboratory investigations using the research instrument.Result: The mean age was 42.7±9.8 years with range from 24 to 64 years and 41.1±9.1 years with range from 26 to 61 years in group-I and group-II respectively. The proportion of male and female patients was similar in both the study groups. Male Female ratio was 1: 7 in both groups. In this study it was observed that hypothyroidism was found 25.0% in group I and 5.0% in group II, which was significantly (p